Enhancement of Maximal Ratio Combiner over Log-Normal Fading Channel using Firefly Algorithm - Ojo, Samson Iyanda; Abolade, Robert Oluwayimika; Salami, Hamed Temitope; Adeyemo, Zachaeus Kayode; Akintoye, Nafiu Olayiwola (Discoveries in Agriculture and Food Sciences, 2019)
Wireless communication system has a great impact in the world of telecommunication and is expected to be a leading role in the developing a nation. However, the system is characterized by multipath propagation effects that lead to signal fluctuation at the receiver, thereby degrading the performance of the system. Maximal Ratio Combiner (MRC) being used to address this problem is characterized with hardware complexity that results in long processing time. Therefore, in this paper enhancement of MRC with closed form expression over Log-Normal fading channel is carried out using Firefly Algorithm (FA) at the receiver. FA create a flashing light in associated with Signal to Noise Ratio (SNR) of the received signal and output the signal with highest SNR. Randomly generated bits used as source data are modulated using M-ary Quadrature Amplitude Modulation (M-QAM) and transmitted over Log-Normal fading channel to generate resultant signals. The resultant signals at varying paths ‘L’ (2, 3, 4) are optimized by FA. The outputs of the FA are combined by MRC to obtain the received signal and converted to baseband through demodulation. A mathematical expression using the Probability Density Function (PDF) of Log-Normal fading channel at varying paths ’L’ for Bit Error Rate (BER) is also derived. The technique is simulated using MATLAB 7.4. The performance is evaluated using Signal-to-Noise Ratio (SNR), Bit Error Rate (BER) and Processing Time (PT). The result shows that, the enhanced MRC (eMRC) gave lower BER values when compared with conventional MRC with reduction in hardware complexity. The eMRC carried out can be used to enhance the performance of wireless communication system.